Nothing comes easy - Singh, Jugjet (2012)
THE Malaysian women start as raging favourites to win gold in the first round of the World League which begins in Kuantan today. This is because the hosts will battle relatively easy teams in the shape of Singapore, Kazakhstan and Sri Lanka over the next three days for a ticket to the tougher Second Round.